Severe Impaired Deambulation in a Patient with Vitamin D and Mineral Deficiency Due to Exocrine Pancreatic Insufficiency - Christensen, Anton Tedja; Østergård, Torben; Andersen, Vibeke (JOP. Journal of the Pancreas, 2011)
<!–[if gte mso 9]> 72 1024x768 <![endif]–><!–[if gte mso 9]> Normal 0 14 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Context Skeletal muscle weakness and impaired gait function are common risk factors for disease and even death. Therefore, identification of the modifiable causes of skeletal muscle weakness should have high priority. Knowledge regarding optimal vitamin D treatment in cases of pancreatic insufficiency is scarce. Case report We report a case of a slow decrease in ability to walk distances more than 100 m during the previous 6 months. Low exocrine pancreatic function resulting in phosphorus, magnesium and vitamin D deficiency was found. Medical treatment with peroral pancreatic enzymes, phosphorus, magnesium and i.m. injections of ergocalciferol (vitamin D2) was initiated. Gait function gradually increased to a walking distance of 1,500-3,000 m along with the normalization of the vitamin D and mineral blood levels. Conclusions Vitamin D deficiency due to exocrine pancreatic insufficiency should be kept in mind as one of the reasons for impaired gait and skeletal muscle weakness.